CONSUMER’S POSITIONING AND PERCEPTION IN DETERMINING SHARIA BANK - Tati Handayani (Fakultas Ekonomi Universitas Negeri Jakarta, 2019)
This study aims to determine how the Positioning of Bank Syariah Mandiri Syariah, Bank Muamalat, BNI Syariah, and BCA Syariah based on community perceptions in Jakarta. In this study also looked at the influence of the role and status as well as beliefs / attitudes towards community perceptions of Islamic Banks in Jakarta. This research is the people of Jakarta, with a sample of customers from 4 Syariah Banks namely Mandiri Syariah Bank, Muamalat Bank, BNI Syariah, and BCA Syariah. Data analysis uses PLS (Partial Least Square), MDS (Multidimensional Scaling) and CA (Correspondence Analysis). The results of this study indicate that the belief / attitude variable significantly influences the perception and the role and status variable does not significantly influence the perception. In the analysis of the positioning results. Bank Muamalat and BNI Syariah are perceived to have consumers in common, BCA Syariah and Bank Syariah Mandiri are perceived as having no similarity with other Islamic banks. To be able to become a good Sharia bank, all sharia banks must be able to improve their positioning properly. Keywords: perception, positioning, Islamic bank